DIVORCE SETTLEMENT THROUGH MEDIATION PROCESS IN LHOKSEUMAWE SHARIA COURT - Faisal, Faisal; Said, Muhammad Helmi MD; Manfarisyah, Manfarisyah; Jumadiah, Jumadiah; Herinawati, Herinawati; Effida, Dara Quthni (Fakultas Hukum, Universitas Diponegoro, 2024)
This study examines the effectiveness of mediators in resolving divorce cases based on the Supreme Court Regulation on Mediation Procedures and the function of mediators to reduce divorce rates. The type of research is empirical juridical, and primary data, and secondary adopts a juridical approach.. This research reveals that the implementation of the Supreme Court Regulation No. 1 of 2016 at the Lhokseumawe Sharia Court has not been maximized so it is necessary to strengthen the education of the judges-mediator regarding how judges handle mediation. In addition, a persuasive approach is needed so that mediation can be run effectively to prevent divorce. The mediator has to maximize his role in reconciling the litigants in the Court so that the parties do not consider mediation as a mere formality. Socialization is needed in the community regarding the importance of resolving disputes peacefully as determined under supreme court regulation.